Durian Tree Watering System Uses Iot And Solar Energy - Hairudin, Muhamad Izzudeen; Mustafa, Mohamad Zaid; AHAD, ROSNEE (Research and Innovation in Technical and Vocational Education and Training, 2023)
When the dry season arrives, the thing that worries the durian planters the most is when the soil of the durian plantation dries up quickly. Therefore, this project can solve the problem by submitting a Durian Tree Irrigation System Using Iot And Solar Energy developed to address the problem of fast drying soil. The ESP2866 used a controller system to interact with the watering system. The development of this project is to ensure that this irrigation system can be controlled with an energy -friendly wireless concept. The Blynk app is used to control the watering system and monitor soil moisture conditions via a smartphone. So, users only need to open the system in their smartphone to set the sensitivity of the sensor and the status of the watering done. The project will also use solar energy which will save the gardeners and the gardeners also do not need to pull the power supply into the garden which is difficult to maintain if there are any problems. The project mainly focuses on watering control system connected to EPS2866 via wireless router. Thus, a wireless router is used to connect the system. In this project as well, a smartphone will act as a controller and a wireless router will act as a medium between the connection and the ESP2866 will act as a signal receiver